Longings for Manila projections of imperialism and decline in the poems of J. Slauerhoff - Van Der Wall, Hidde (Philippine Studies: Historical and Ethnographic Viewpoints, 2016)
The Dutch poet Jan Jacob Slauerhoff (1898–1936) featured Manila in three poems written in the late 1920s. These poems present the city as the decaying remnant of a deceased empire. Manila appears as a memory site of Spain’s bygone world dominance, resonates with the discourse of the “decline of the West,” and bears parallels to an image of a decaying Dutch empire. The city functions as a screen against which cultural images derived from the author’s personal European context are projected: cultural pessimism and colonial decline.